Sex differences in sleep apnea and comorbid neurodegenerative diseases - Snyder, Brina; Cunningham, Rebecca L. (Steroids, 2018)
Sleep apnea is a disorder, which increasingly affects people worldwide. Whether the associated hypoxic events during sleep are central or obstructive in origin, the end result is excessive daytime sleepiness and an increased risk for several comorbidities, such as cardiovascular and neurodegenerative disorders. Sleep apnea is diagnosed more frequently in men than women, suggesting a role of sex hormones in the pathology of the disease. Furthermore, there are sex differences in the development and progression of comorbid diseases associated with sleep apnea. Therefore, treatment of sleep apnea may be clinically relevant for prevention of subsequent sex-specific comorbid disorders. While the impact sleep apnea has on cardiovascular events has been the subject of many research studies, the role of sleep apnea in neurodegeneration is less established. Here we review known risk factors for sleep apnea and the implications of the observed sex differences in this disease. We also summarize the evidence and mechanisms for how sleep apnea may contribute to the onset of neurodegenerative disorders, such as Alzheimer’s disease and Parkinson’s disease.